Surviving autocracy - Gessen, Masha (New York : Riverhead Books, 2020)
"An analysis of the destruction the Trump administration has waged on our institutions, the cultural norms we hoped would save us, and our very sense of identity"--
What do we call it? -- Waiting for the Reichstag fire -- The Styrofoam president -- We could call it a kakistocracy -- We could call it corruption -- We could call it aspirational autocracy -- We could pretend he is an alien, or call it the government of destruction -- The death of dignity -- Mueller did not save us -- Institutions have not saved us -- Words have meaning, or they ought to -- The power lie -- The tweet trap -- Normalization is (almost) unavoidable -- Resisting Trump's war on the media -- How politics dies -- A white male supremacist president -- "Throwing off the mask of hypocrisy" -- The antipolitics of fear -- Confronting civil society -- The power of moral authority -- Who is "us"? And who are we?
Includes bibliographical references.
HB
Keywords: Trump, Donald, -- 1946- -- Influence; Authoritarianism -- United States; Dictatorship -- United States; Political culture -- United States; United States -- Politics and government -- 2017-